Assessment of public involvement in urban governance: case study in Putrajaya - Raduwan, Afifah; Ismail, Sumarni (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The urbanization process in the 21st century is no longer suitable for the rehabilitation of existing cities as it is already dense and complex and has very limited development potential. Therefore, the new planned cities or township has become a better option as it is more organized and well-planned. However, the creation of planned cities should be made more rigorous and comprehensive as it involves migration of communities who have to adapt to the physical urban design, the economy and social activities. Thus, the main purpose of this study is to assess the social impact of this new planned city of Malaysia – Putrajaya including the satisfaction level regarding to physical urban design, socio-economic as well as their involvement in decision-making process in urban governance towards sustainable living environment.